DIVERSIFIKASI PENGGUNAAN INSTRUMEN HUKUM DALAM PENEGAKAN HUKUM TERHADAP PRAKTIK BINARY OPTION DI INDONESIA - Bryan DWT Simalango (2023)
In today's modern era, there are many online trading systems available on the Internet. Not a few people who are victims of criminal acts of fraud from online trading systems that have sprung up on the internet without a safe system and legality. One of the systems or practices prohibited by the government is Binary Option Practice. Through this article, it is hoped that the public will recognize and understand the dangers of binary options. Binary option is a system that requires consumers or users to guess the price of the asset they choose within a certain period of time. To attract public attention and trust, Binary Option practice activities use affiliates, namely influencers, to promote Binary Option practices in the community. The criminal act of fraud committed by the perpetrator is very detrimental to the general public and the perpetrator certainly gets a very fantastic profit. Therefore, Binary Options are included in the Gambling category. In a case that has been tried and has received a verdict, the suspect violated Article 28 paragraph (1) of the ITE Law and the crime of money laundering was sentenced to 10 years in prison and paid a fine of 5 billion rupiah and returned all costs of compensation/restitution to the victim through an appeal decision and amending the previous district court decision. In addition to violating the law above, there are still several laws or regulations that regulate the prohibition of illegal commodity trading activities.